Effect of Dual-Flow Channel Structures on Electrochemical CO2 Reduction in Proton Exchange Membrane Electrolyzers - Na, Youngseung; Ha, Min Gwan; Park, Hyun S.; Park, Hee Young; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Lee, So Young; Jang, Jong Hyun (Frontiers in Energy Research, 2022)
Greenhouse gases such as carbon dioxide and methane are responsible for intensifying global warming. Consequently, a reduction in power plant outputs and an increase in capture and storage on-site are required to reduce greenhouse gas emissions. Recently, research has focused on an electrochemical CO2 reduction method because the amount of CO2 reduction can be controlled by adjusting the operating voltage. However, to scale up the electrochemical system while maintaining a high conversion rate in a large cell, a suitable flow field of the cell must be optimized. The transparent cell structure presented in this study allows visualization of the distribution of the two-phase flow. Accordingly, dual-flow channels consisting of main and sub-channels have been designed. Furthermore, multiple configurations of the dual-flow channels and locations of the catalyst layer have been compared. The interdigitated sub-channels and inverted layered cell structures can supply gas and liquid to the catalyst layer via distinct pathways, allowing for uniform flow distribution to each channel.